Conceptualization of Accounting Ethics in Facing the Crisis of Global Economic Morality in the Modern Era - Olasoji Olubiyi, Timilehin (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2025)
This paper explores the conceptualization of accounting ethics in response to the moral crises within the global economic landscape. As financial markets become increasingly interconnected, accounting professionals are faced with complex ethical challenges that demand an evolving approach to decision-making and reporting. This study reviews the key ethical issues confronting accountants, including the pressures of corporate governance, the ethical implications of globalization, technological advancements, and the need for continuous ethics education. By analyzing case studies of corporate scandals, such as Enron and Lehman Brothers, the paper highlights how ethical lapses in accounting can lead to severe financial instability and loss of public trust. The findings suggest that the accounting profession must adopt a more proactive approach to ethics, integrating stronger corporate governance, enhanced transparency, and improved education to address emerging ethical dilemmas. The paper proposes a framework for strengthening accounting ethics, emphasizing the need for a unified approach to global standards, responsible technological innovation, and a culture of ethical accountability within organizations. Ultimately, the study aims to foster a more ethical and transparent accounting profession that can contribute to the stability and sustainability of the global economy.